SPECTRUM AND OUTCOMES OF OPPORTUNISTIC INFECTIONS IN PATIENTS WITH TYPE 2 DIABETES MELLITUS: A HOSPITAL-BASED OBSERVATIONAL STUDY IN NORTH KARNATAKA - SIDDAGANGA SANGAVI; RACHANA Y HEBBAL; VRUSHALI MOHITE; VIJAYALAKSHMI KP (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: Patients with type 2 diabetes mellitus (T2DM) are at increased risk for opportunistic infections due to impaired immune responses and chronic hyperglycemia. This study aimed to assess the spectrum, burden, and clinical outcomes of opportunistic infections in T2DM patients at a tertiary care hospital. Methods: A hospital-based observational study was conducted from August 2024 to January 2025, involving 141 T2DM patients with infections out of a total of 440 diabetic patients who attended inpatient and outpatient services. Demographic data, infection types, glycemic control (glycosylated hemoglobin [HbA1c]), comorbidities, treatment modalities, and outcomes were analyzed. Chi-square testing was used to assess associations between infection types and sex. Results: The prevalence of infections among T2DM patients was 32.04%. The majority were aged 51–60 years (70.2%), and males were slightly more affected (53.2%). Most infections occurred in patients with a diabetes duration of 6–10 years and HbA1c levels between 9 and 11%. Acute gastroenteritis (21.3%), urinary tract infections (34%), and pneumonia (10.6%) were the most common. Pneumonia showed a significant association with male sex (p=0.026). Hypertension was the most frequent comorbidity (90.7%). Overall, 89.7% of patients recovered, whereas 10.3% developed complications; no mortality was recorded. Longer hospital stays were significantly associated with poor glycemic control (HbA1c >8.5%, p=0.03). Conclusion: Opportunistic infections are common in T2DM, especially among patients with longer disease duration and poor glycemic control. Early recognition and optimized diabetes management are essential for reducing infection-related complications and hospitalization.